Laparoscopic Gastrectomy for Cancer: Cut Down Complications to Unveil Positive Results of Minimally Invasive Approach - Bjelovic, Milos; Veselinovic, Milan; Gunjic, Dragan; Bukumiric, Zoran; Babic, Tamara; Vlajic, Radmila; Potkonjak, Dario (Frontiers in Oncology, 2022)
Several randomized control trials and meta-analysis have confirmed the advantages of laparoscopic surgery in early gastric cancer and there are indications that this may also apply in advanced distal gastric cancer. Study objective was to evaluate the safety and effectiveness of the laparoscopic gastrectomy, in comparison to open gastrectomy, in the management of locally advanced gastric cancer. The single center, case control study, included 204 patients, in conveyance sampling, who underwent radical gastrectomy for the locally advanced gastric cancer. Out of 204 patients, 102 underwent laparoscopic gastrectomy (LG), and 102 patients underwent open gastrectomy (OG). Primary endpoints were safety endpoints i.e. complication rates, reoperation rates and 30-day mortality rates. Secondary endpoints were efficacy endpoints, including perioperative characteristics and oncological outcomes. Even though the overall complication rate was higher in OG group, compared to LG group (30.4% and 19.6% respectively) the difference between groups did not reach statistical significance (p=0.075). No significant difference was identified in reoperation rates and 30-day mortality rates. Time spent in the Intensive Care Unit (ICU) and overall hospital stay were shorter in the LG group compared to OG group (p<0.001). Although the number of retrieved lymph nodes is oncologically adequate in both groups, the median number is higher in the OG group (35 vs. 29; p=0.024). Resection margins came out to be negative in 92% of patients in the LG group and 73.1% in the OG group (p<0.001). Study demonstrated statistically longer survival rates for the patients in the laparoscopic group, which particularly applies to patients in the most prevalent, third stage of the disease. When patients with Clavien-Dindo grade ≥II were excluded from the survival analysis, further divergence of survival curves was observed. In conclusion, laparoscopic gastrectomy can be safely performed in patients with locally advanced gastric cancer and accomplish the oncologic standard with short ICU and overall hospital stay. Since postoperative complications could affect overall treatment results and diminish and blur positive effect of minimally invasive approach, further clinical investigations should be focused on the patients with no surgical complications, and clinical practice to cut down the prevalence of complications.